Potential Of Citronella Oil As Rodent Repellent Measured As Aversion To Food (Applied Biological Research, 2014)
Repellents act by stimulating the primary or secondary defense  mechanisms, causing the food to be rejected. Mature and healthy house  rats, Rattus rattus, of both the sexes, were exposed to 5, 10, and 20%  citronella oil applied as paint in laboratory pens in choice with no oil.  Each concentration was applied through 3 different modes of application  (daily, once and alternatively in a week). Repellent effect of oil was  assessed by comparing food consumption from treatedsides with those  of untreated sides. The food consumption was recorded over a period of  4 days. In overall, food consumption was significantly (p≤ 0.05) lower  from treatmentside compared to the untreated side indicating significant  repellent effect of the oil. Repellent effect of oil, however, did not differ significantly between the two sexes. Significant difference in average  percent repellent effect between 5 and 10% concentrations was observed  when oil was applied daily in both female and male rats with higher  effect of treatment at 10%. The studies revealed higher potential of daily  application of citronella oil as paint in repelling away rats of both sexes.
Keywords: Citronella oil; food consumption; paint; Rattus rattus; repellency